Cultivated autologous oral mucosal epithelial transplantation - S. A. Borzenok; B. E. Malyugin; M. Yu. Gerasimov; D. S. Ostrovsky (Вестник трансплантологии и искусственных органов)
According to the World Health Organization, corneal blindness is the fourth most common cause of blindness and visual impairment worldwide. In Russia, up to 18% of blindness is caused by corneal damage. Limbal stem cell deficiency (LSCD) is one of the causes of corneal blindness and visual impairment due to anterior epithelial replacement with fibrovascular pannus. Bilateral LSCD may develop in patients with aniridia, Steven-Jones syndrome, and severe corneal burns of both eyes, leading to severe decrease in visual acuity in both eyes and, as a consequence, physical disability associated with blindness. In such cases, cell therapy, based on autologous oral epithelial culture as an alternative to allogeneic limbus transplants, is proposed for reconstruction of the anterior corneal epithelium. This new treatment method promotes corneal reepithelization, better visual acuity, reduced nonspecific ocular complaints and improved quality of life of patients. The effectiveness and significant increase in the frequency of transparent engraftment of donor corneas after cell therapy drives huge interest in this topic all over the world. This review presents literature data on the features of histotopography and methods for obtaining a cultured autologous oral mucosal epithelium, on cell markers that are used to identify epithelial cells, and on methods for creating cell grafts for subsequent transplantation to the corneal surface in LSCD patients.